1976
DOI: 10.1530/jrf.0.0480307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prolactin and growth hormone on prolactin and LH receptors in the dwarf mouse

Abstract: Dwarf mice (DW/J; dw/dw) which exhibit a deficiency of prolactin and GH secretion were treated for 8 days with ovine prolactin and/or human GH (10 or 20 \g=m\g/day) and the effect on hepatic and testicular prolactin receptors was investigated. In both sexes there was a significant increase in body weight after all hormone treatments, but an increment in testicular weight was observed only after prolactin administration. Prolactin treatment increased the specific binding % of prolactin in liver membranes in fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…However, plasma concentrations of prolactin were related to the onset of spermatogenesis rather than as a result of hemicastration. The mechanism by which prolactin influences early pubertal Sertoli cell function and spermatogenesis, although unclear, appears to be by indirectly influencing the receptiveness of Leydig cells to LH stimulation and androgen secretion (Bohnet & Friesen, 1976;Zipf et al, 1978;Stoud et al, 1985). …”
Section: Discussionmentioning
confidence: 99%
“…However, plasma concentrations of prolactin were related to the onset of spermatogenesis rather than as a result of hemicastration. The mechanism by which prolactin influences early pubertal Sertoli cell function and spermatogenesis, although unclear, appears to be by indirectly influencing the receptiveness of Leydig cells to LH stimulation and androgen secretion (Bohnet & Friesen, 1976;Zipf et al, 1978;Stoud et al, 1985). …”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated that a lack in serum prolactin is associated to a loss in testicular LH receptors and these are recovered only after treatment with prolactin [7,321. A decrease in the number of LH receptors due to hypoprolactinemia may account for diminished serum testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…The prolacin receptor is generally considered to be upward by the homologous hormone in rat liver or ovary Bohnet and Friesen 1976), which is different from regulation of LH or FSH receptors (Conti et al 1977;Ireland and Richards 1978). It is interesting that a strong negative correlation was observed between the prolactin receptor and serum FSH level.…”
Section: Discussionmentioning
confidence: 99%